Camouflaged angiogenic BMP-2 functions exposed by pico-paracrine biohybrids - Jennissen, Herbert P. (Frontiers in Bioengineering and Biotechnology, 2023)
The constant release of human bone morphogenetic protein 2 (rhBMP-2) in the picomolar range (Pico-Stat) from PDLLA-biohybrids led to the detection of intrinsic novel pro- and anti-angiogenic functions of this cytokine. As integrant part in this perspective of previous work, first evidence for the binding of rhBMP-2, as an inverse agonist, to allosteric angiogenic receptors in cocultures of human endothelial cells is reported.